ASSIGNMENT MODEL-BASED AND INTEGRATED PROCESS IMPROVEMENT (MIPI) TO INTEGRATE WASTE MANAGEMENT SYSTEM IN TPST BANTARGEBANG-BEKASI, WEST JAVA- INDONESIA - Lien Herliani Kusumah; Didik Syaiful Bachri; Gendut Suprayitno (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. The waste management in Bantargebang has been planned for 15 yearsand should be improved in order to meet the needs of the stakeholders. The studyis done to find the right method to be used for integrating the waste managementin Bantargebang site. The method is a review of previous studies related toimprovement in waste management and business processes. The result suggeststhat the mapping of the process needs to be done on the waste managementsystem and using the Model-Based Integrated Process Improvement (MIPI) whichdeveloped by Adesola et al. (2006) to improve the process.Keywords: waste management, business process mapping, process, Model-Basedand Integrated Process Improvement (MIPI)